Implementation of Good Village Governance Principles in Realizing an Anti-Corruption Village: A Study in Hanura Village, Teluk Pandan Subdistrict, Pesawaran Regency - Romadhona, Nabila Aisyah; Meutia, Intan Fitri; Hermawan, Dedy; Kagungan, Dian (Utan Kayu Publishing, 2025)
This study aims to analyze and explore the implementation and supporting factors of good village governance principles in Hanura Village, Teluk Pandan District, Pesawaran Regency, in the effort to realize an Anti-Corruption Village. The research method used is descriptive with a qualitative approach. Data were collected through observation, documentation, and interviews. The results show that the principle of transparency is manifested through public information disclosure, both online and offline; the principle of accountability is implemented through vertical accountability reports and horizontal accountability mechanisms; while the principle of participation is realized through community involvement in planning, implementation, benefit reception, and evaluation of development programs. The supporting factors include the strong commitment of the village head’s leadership, regulatory and digital system support, and the local community’s culture of mutual cooperation (gotong royong). The implementation of good village governance principles in Hanura Village has been effective and has directly contributed to its designation as an Anti-Corruption Village. However, the application of good village governance in Hanura Village still faces obstacles, particularly the low level of digital literacy and limited socialization, causing the digitalization programs to be less inclusive and somewhat more advanced than the readiness of the village community as the main users.